PERAN PEKERJA SOSIAL DALAM REHABILITASI SOSIAL PADA PENYANDANG DISABILITAS MENTAL DI PANTI SOSIAL BINA LARAS PAMBELUM - Rahayu, Marina; Munawarah, Hanikhatul; Sriyani, Sriyani; Putri Septiani, Riri Eka; Putri, Linni Turia; Pratiwi, Melinia; Julianto, Yolgi; Rizka, Ramadhanti; Ateza Sembiring, Vio; Irfan, Muhammad (Jurnal Bimbingan dan Konseling Pandohop, 2022)
A person with mental disability is someone who has a brain disorder characterized by disturbed emotions, thought processes, behaviors and perceptions (sensory capture) which can cause stress and suffering for the person concerned. Therefore, people with mental disabilities need social rehabilitation services to restore their social functions through orphanages. Panti Sosial Bina Laras (PSBL) Pambelum Palangka Raya has the task of organizing some operational technical activities in providing curative, rehabilitative, promotive social service and rehabilitation guidance in the form of basic knowledge guidance on physical, mental, social, and skills training. need social workers. The purpose of this study is to provide an overview of the services, programs and social rehabilitation activities carried out at PSBL Pambelum. The research method used is a qualitative method with data collection by interview and observation. It is hoped that after knowing the description of services in PSBL, the community will know the importance of social rehabilitation for people with mental disabilities, so that after completing social rehabilitation they can be accepted back into their families and communities.